AN OVERVIEW OF THE BANKING SYSTEM IN SYRIA AFTER A DECADE OF UNREST - Omar Farouk Al Mashhour; Muhammad Imam Asalie; Ahmad Shamsul Abd Aziz; Nor Azlina Mohd Noor (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
After a decade of crippling international sanctions and devastating conflict, the Syrian economy has been largely in shambles. Nevertheless, the Syrian banking industry has largely weathered the storm. This article attempts to illustrate a comprehensive view of the banking sector in Syria and how well has one of the oldest banking systems in the middle east fared over the years and how has it survived the seemingly insurmountable challenges. Additionally, The article targets to show the role of the central bank of Syria in supervising the banking industry as well as a view on the recent development of the legal and financial orientation. The researchers have faced issues related to the absence of information due to its limits on what the central bank is publishing. Also, it is found that lack of English annual reports and missing reports for some years, will lower the chances of attracting investors. The article suggested a set of recommendations that may elevate the condition of the Syrian banking system by issuing a new law enforcement division to track down any unlawful activities.